2021
DOI: 10.1111/acfi.12756
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of accounting students’ undergraduate learning satisfaction

Abstract: This paper examines factors that influence the learning satisfaction of business school students in general and accounting students in particular. Guided by both the literature and the findings from a series of eight focus group sessions involving 43 university undergraduates, a research instrument capable of examining factors associated with student learning satisfaction was designed. Survey responses from 548 students generated seven factors of student satisfaction, with students attributing high importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 55 publications
1
35
0
2
Order By: Relevance
“…Por último, teniendo en cuenta las variables predictoras más relevantes, el estudio de las diferencias por género muestra que solo existen diferencias estadísticamente significativas en la variable de satisfacción con la elección de la titulación, siendo las mujeres las que presentan puntuaciones más altas en este ítem. Según Adler et al (2021), en un estudio realizado para observar los factores que influían en la satisfacción de aprendizaje de los estudiantes universitarios, el género y la especialización del estudiante suponían diferencias entre los diversos factores de estudio y la satisfacción de aprendizaje informada por los estudiantes. Además, estos resultados podrían servir para complementar los obtenidos por García y Adrogué (2015), cuya investigación observó que los varones presentaban una mayor probabilidad de abandonar los estudios superiores, lo cual podría indicar una cierta influencia en este fenómeno del papel de la satisfacción con los estudios cursados.…”
Section: Discussionunclassified
“…Por último, teniendo en cuenta las variables predictoras más relevantes, el estudio de las diferencias por género muestra que solo existen diferencias estadísticamente significativas en la variable de satisfacción con la elección de la titulación, siendo las mujeres las que presentan puntuaciones más altas en este ítem. Según Adler et al (2021), en un estudio realizado para observar los factores que influían en la satisfacción de aprendizaje de los estudiantes universitarios, el género y la especialización del estudiante suponían diferencias entre los diversos factores de estudio y la satisfacción de aprendizaje informada por los estudiantes. Además, estos resultados podrían servir para complementar los obtenidos por García y Adrogué (2015), cuya investigación observó que los varones presentaban una mayor probabilidad de abandonar los estudios superiores, lo cual podría indicar una cierta influencia en este fenómeno del papel de la satisfacción con los estudios cursados.…”
Section: Discussionunclassified
“…The factors that are still the same for the success of lecturers are lecturers' materials, which students expect to be able to understand clearly, as demonstrated in the studies of Gopal, Singh and Aggarwal (2021) and Adler et al (2021). These studies have indicated that lecturers are expected to have sufficient communication skills and enthusiasm for teaching (Gopal, Singh and Aggarwal, 2021;Adler et al, 2021;Butler, Samuels and Peditto, 2021).…”
Section: Expectations Of Lecturers During the Covid-19 Pandemicmentioning
confidence: 99%
“…There have been many studies that have raised this shift in student satisfaction regarding lecturers during the pandemic, in various countries, including Egypt (Basuony et al, 2021), China (Lei and So, 2021), Sri Lanka (Hettiarachchi et al, 2021), Thailand and Indonesia (Darawong and Widayati, 2021), New Zealand (Adler et al, 2021), and Canada (Butler, Samuels and Peditto, 2021). Almost all of these studies used quantitative tools in the form of surveys.…”
Section: Expectations Of Lecturers During the Covid-19 Pandemicmentioning
confidence: 99%
“…About 35 minutes were spent in each focus group session. As a group or as an individual, all participants wrote down their thoughts on the following: "(1) what promotes a satisfactory learning result; (2) what contributes to successful student learning outcomes; and (3) how the environment contributes to their learning effectiveness." "A total of nine factors, researchers discovered (see Table 1), reveals that the focus groups were unanimous in their agreement with the literature review's conclusions."…”
Section: Focus Groupsmentioning
confidence: 99%
“…First and foremost, it fails to see a strategy to raise student accomplishment. Preliminary research repeatedly reveals that student happiness, student motivation, student retention, and student achievement are all linked (Adler, et al 2021). (Ginnetti, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%